Peru : A Handwashing Behavior Change Journey - World Bank (Washington, DC, 2012)
In 2003, a national multi-sectorial Handwashing Initiative (HWI) was created in Peru to increase handwashing with soap among mothers and children. The early years of the HWI focused on laying groundwork, including a formative research study in 2004; the creation of a consultative committee by the Ministry of Health (MoH); and a national decree formalizing the HWI. The Water and Sanitation program (WSP) has coordinated the HWI since its inception. This learning note profiles the behavior change component of the second phase with a focus on how it was designed, implemented, and monitored. Challenges and lessons learned are included to assist program managers as they make decisions to develop and manage a handwashing promotion initiative. Peru provides an interesting case study because the intervention itself is interwoven with efforts to strengthen capacity, policies, partnerships, and other aspects of the enabling environment required to sustain handwashing with soap programs. Though detangling these various program components is a challenge, this note on the behavior change journey attempts to do so.